2000
DOI: 10.1046/j.1365-2435.2000.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses to a climate‐warming manipulation for contrasting meadow species in the Rocky Mountains, Colorado, USA

Abstract: Summary 1.Microclimate was measured and photosynthetic responses to a climate warming manipulation were compared for the evergreen shrub Artemisia tridentata and the herbaceous forb Erigeron speciosus in the Rocky Mountains, Colorado, USA. 2. Soil was warmer and drier under infra-red heaters compared with control plots. 3. Midday xylem pressure potential did not differ for A. tridentata on heated vs control plots but was lower for E. speciosus on heated plots compared with controls. Leaf temperatures did not v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 35 publications
6
46
0
5
Order By: Relevance
“…Indeed, our initial results from a warming experiment in the eastern Tibetan Plateau indicated an increase in soil temperature and a decrease in soil moisture content for plots in OTC, and experimental warming increased the cover degree and biomass accumulation in the grasses, but reduced them in the forbs (Shi et al 2008). Similar responses of different plant groups to a warming experiment have also been demonstrated in the Tibetan Plateau (Zhang andWelker ---1996, Zhou et al 2000) and other cold regions (Harte and Shaw 1995, Arft et al 1999, Henry and Molau 1997, Loik et al 2000.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Indeed, our initial results from a warming experiment in the eastern Tibetan Plateau indicated an increase in soil temperature and a decrease in soil moisture content for plots in OTC, and experimental warming increased the cover degree and biomass accumulation in the grasses, but reduced them in the forbs (Shi et al 2008). Similar responses of different plant groups to a warming experiment have also been demonstrated in the Tibetan Plateau (Zhang andWelker ---1996, Zhou et al 2000) and other cold regions (Harte and Shaw 1995, Arft et al 1999, Henry and Molau 1997, Loik et al 2000.…”
Section: Introductionsupporting
confidence: 62%
“…The positive effects of warming on gas exchange of some plant species had been reported by other studies (Chapin and Shaver 1996, Bergh and Linder 1999, Loik et al 2004. However, the gas exchange of P. anserina significantly decreased in the warming treatment and this could be attributed to the effect of warming on soil drying, which had been reported by Loik et al (2000). Giorio et al (1999) demonstrated that the decrease of gas exchange under the condition of water stress owed to the limitation of stomata or photosynthetic organelles.…”
Section: Photosynthetic Parametersmentioning
confidence: 54%
See 2 more Smart Citations
“…Loik & Redar 2003, Loik et al 2004, Sierra-Almeida et al 2009). Por ejemplo, Loik et al (2000) encontraron que la conductancia estomática y la tasa de fotosíntesis de Erigeron speciosus y Artemisia tridentata disminuyeron con el aumento de la temperatura, el que a su vez produjo una mayor desecación del suelo.…”
Section: Introductionunclassified